2021
DOI: 10.1002/jsfa.11084
|View full text |Cite
|
Sign up to set email alerts
|

Functionality and consumer acceptability of low‐fat breakfast sausages processed with non‐meat ingredients of pulse derivatives

Abstract: BACKGROUND Owing to recent changes in consumer eating behaviours as well as potential cost savings for processors, pulse ingredients are finding more application in the meat processing industry. In this study, pea ingredients (pea fibre, FB; pea starch, ST; pea flour, PF) and chickpea flour (CF) were used, at 4% addition level, as fat replacers in low‐fat breakfast sausages. The impact of these substitutions on processing and sensory characteristics of breakfast sausage was evaluated. RESULTS While reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…Pulse proteins are often used as extenders in manufacturing meat products 23 . Pietrasik and Soladoye 24 reported that adding pea fiber, flour, and starch (4%) reduced the CL of low‐fat breakfast sausages. Pork low‐fat burgers with pulse flours derived from pea, chickpea, lentil, or bean (80 or 150 g kg −1 ) had higher CYs compared with commercial or control products 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulse proteins are often used as extenders in manufacturing meat products 23 . Pietrasik and Soladoye 24 reported that adding pea fiber, flour, and starch (4%) reduced the CL of low‐fat breakfast sausages. Pork low‐fat burgers with pulse flours derived from pea, chickpea, lentil, or bean (80 or 150 g kg −1 ) had higher CYs compared with commercial or control products 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Ahn et al 44 reported no effect on the CIE L* of low-fat pork sausages when SPI (1.5 or 3%) was added; however, the CIE a* decreased and the CIE b* increased. Pietrasik and Soladoye 24 reported that the color values of cooked low-fat breakfast sausages with pea and chickpea flour 1.…”
Section: Color Measurementmentioning
confidence: 99%
“…However, it is important to remember, that in addition to providing energy, fats strongly influence the consistency, taste and appearance of a product, in addition to its characteristic structure and flavour [ 120 ]. Therefore, limiting the SFA content in a product may involve the need to use fat substitutes to maintain its sensory attractiveness [ 120 , 121 ]. Most importantly, these substitutes will also affect the energy content of the product and, thus, its overall Nutri-Score rating.…”
Section: Discussionmentioning
confidence: 99%
“…Para satisfacer la demanda del mercado, es necesario contar con ingredientes proteicos de origen vegetal que compitan o tengan una calidad y funcionalidad mejorada en comparación con los ingredientes tradicionales de proteínas animales (Flores & Piornos, 2021b). Debido a los cambios en comportamientos alimentarios de muchos consumidores, así como posibles ahorros de costos para los procesadores, los ingredientes de legumbres están encontrando más aplicación en la carne industria de procesos (Pietrasik & Soladoye, 2021a) orientadas a la producción de alimentos más saludables para lo cual se han adoptado diferentes estrategias tal como se muestra en la Figura 3. Sin embargo, el perfil de aroma de los fermentados tradicionales de salchichas de carne es difícil de alcanzar.…”
Section: Fibras Como Sustitutos De Carneunclassified